Analytical Calculation of Coupled Magnetothermal Problem in Gas Insulated Transmission Lines - Guoxia Sun; Xiangchao Jin; Zhiyang Xie (Universitas Ahmad Dahlan, 2013)
Gas insulated transmission lines (GIL) are a new technology for transmitting power over long distances. In this paper, an analytical method (AM) is proposed to investigate the coupled magnetothermal problem in GIL. Kelvin functions are employed to calculate the skin effect coefficients of the conductor and the enclosure. The calculated power losses are used as heat source input for the thermal analysis. Considering the convective and radiation heat transfer effects, the heat balance equations on the surface of the conductor and the enclosure are established, respectively. Temperature rise of the GIL at different operation conditions are investigated. The proposed method is validated against the finite element method (FEM). The simplicity of the approach makes it attractive for self-made software implementation in the thermal design and the condition monitoring of GIL.